The role of middle management in strategy work - Ferkic, Lorena (My University, 2019)
Strategy work is a significant part of a company’s competitiveness and therefore, the success of its implementation process is crucially important. Middle managers act as an information intermediary and influencers between top management and subordinates, which highlights necessary to study practices that improve their strategic skills. Because of their position in the company, the role of middle managers as a strategic resource is significant. Incoherent strategic communication can be damaging to the company, as it should provide the desired direction for the company’s operation. Balancing between understanding top managements’ thinking and consciously affecting subordinates’ mindset is often challenging for middle management. Therefore, this study focuses on contributing strategy work, which considers conditions, practices, and abilities that have an impact on middle management’s role. Middle managers should continuously improve their interaction skills to effectively communicate the objectives and with sensegiving effect employees strategy understanding. Employee’s perspective on strategy is based on the daily discussion and practices related to strategy work, therefore companies must pay more attention to middle lines rhetoric know-how. A theoretical framework is Strategy as practice- research, which highlights actions, activities, and actors. It considers interaction as most important factor in the interpretation and concentrates on actions guiding strategy work. The study is a qualitative case study, which is based on interviews and observations. The observations indicate that the top management should continuously support middle managers in their role with informal discussion and participative strategy work. When middle managers acknowledge their role in the strategy work and have interpreted the strategy, their role is to have open and active communication with employees, be able to set clear goals, use right terminology in discussion, be persuasive and lead employees by example. Middle managers should pursue to connect strategy to daily activities and have consistent strategy practices.
Keywords: Strategy; Middle management; Strategy as practice; Sensegiving; Strategy practices; Strategic communication; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|